Influence of Perceived Legitimacy and Perceived Value of Professional Association Members on Attitudinal Loyalty - María-Elena Sánchez-del-Río-Vázquez; Carlos Rodríguez-Rad; Manuel Orta-Pérez; Maria-Ángeles Revilla-Camacho (Administrative Sciences)
This article explores the discoveries related to organizational legitimacy, focusing on its three key types: pragmatic, moral, and cognitive. It examines how perceived value plays a crucial role in the generation of legitimacy and its direct impact on attitudinal loyalty. The study, based on a survey of 156 members of the Professional Association of Economists of Seville, demonstrates the significant influence of perceived value and legitimacy on the three dimensions of organizational legitimacy and attitudinal loyalty. Based on the findings, the paper recommends a management approach that emphasizes perceived value to reinforce legitimacy, which in turn strengthens loyalty. Another important contribution of our work is that it fills a gap in the literature related to professional association membership loyalty and its antecedents. Further research is suggested to investigate the causes and effects of legitimacy in different organizational contexts.